Entre divisas, divisores e um massacre: a emancipação da não construída cidade de Ipatinga-MG - Freitas, Geraldo Vinícius Ribeiro (2012)
This study aims to construct the History of Ipatinga-MG, with respect to the plurality of agents and events that occurred between 1950 and 1963. The priority is finding two districts of Coronel Fabriciano, which integrate the new city when happened the emancipation of Ipatinga in 1964, constructing the oldest part of its history. In 1958 starts the construction of the Usina Intendente Câmara, which was the first unit of Usiminas S/A. As construction of this plant, part of the history of this city is conditioned to narrate what existed in the Ipatinga village, which is today a region which has become the center since 1922 on the banks of the railroad Vitória-Minas. The Água Limpa village, named today Barra Alegre is considered the oldest near the EFVM, but its history is narrated without much detail. This work intends to reflect on political and human communication these two places had a long time before the arrival of Usiminas until the incident known as the Massacre de Ipatinga , which would be decisive for the emancipation of that place, although it isn‟t recognized. The effort of understanding and how the two districts previously communicated to the capitalist project is what led to a fast population growth from the 1960s. This story‟s fraction of Ipatinga is less put in evidence. Therefore, we prioritize the life of older people living in the region without being aware of how their lives would change dramatically in touch with new characters A variety of human relations was put aside for building a city that makes the Steel of their of human and political investment merchandizing.